Arborizaciones urbanas en clima cálido (2007)
In many Colombian cities, urban forestry is the result of tree planting policies based on introduced species. Cities cut apart original ecosystems, causing alterations, disturbances and deterioration, and because most of the tree populations on urban settings are non native varieties, fragmentation ofthe ecosystem does not diminish. Our results depict that introduced species are, in fact, dominant in many Colombian cities and, because those do not provide food to native fauna (avifauna and small mammals); although they provide some ornamental and environmental services, they do not contributeto the connectivity of fragmented ecosystems caused by urban development.